Sustainable development in the context of pandemic: the impact of COVID-19 pandemic on green investment - He, Yu; Fu, Lin; Li, Tao; Wei, Ran (Frontiers in Ecology and Evolution, 2024)
Promoting green investment is the inevitable choice for sustainable economics against climate change. We examine how the COVID-19 pandemic affected corporate green investment. Using a sample of publicly listed firms in China, we document the negative and significant effect of the COVID-19 pandemic on corporate green investment. Further analyses suggest that the COVID-19 pandemic impeded corporate green investment by exacerbating firms' financial constraints. We also find that the COVID-19 pandemic had no significant effect on total investment, suggesting that the pandemic shock only changed investment structure. In summary, our findings reveal the real effects of the COVID-19 pandemic on green development at the firm level.